TEACHING READING COMPREHENSION THROUGH THE THINK PAIR SHARE TECHNIQUE - Nia Febriyanti (Lingustic, Literature and English Education, 2023)
Teaching reading is not easy for EFL learner, students quick bored because they less vocabulary so difficult to get the point, so the teacher must has strategies in teaching. This article shares how should do teacher’s teach reading comprehension using the think pair share technique. The strategies in this method create the students’ interaction between teacher and students to be active.